Role of XUV Photons in Atomic High-Order Above-Threshold Ionization Processes in IR＋XUV Two-Color Laser Fields - 张奎;刘敏;王兵兵;郭迎春;严宗朝;陈京;柳晓军 (Chinese physics letters, 2017)
We investigate the above-threshold ionization of an atom in a combined infrared （IR） and extreme ultraviolet （XUV） two-color laser field and focus on the role of XUV field in the high-order above-threshold ionization （HATI） process. It is demonstrated that, in stark contrast to previous studies, the XUV laser may play a significant role in atomic HATI process, and in particular, the XUV laser can accelerate the ionized electron in a quantized way during the collision between the electron and its parent ion. This process cannot be explained by the elassical three-step model Our results indicate that the previously well-established concept that HATI is an elastic recollision process is broken down.